2018
DOI: 10.1007/s00706-018-2229-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile fraction of sweetie (Citrus maxima × Citrus paradisi) and its parent fruit using proton transfer reaction mass spectrometry

Abstract: The quality of the fruit is affected by several main ingredients and the aroma plays a fundamental role during the selection of fruit by consumers. In the case where several fruit have similar aromas and only one of them has specific health properties, it is very important to find the differences in the volatile organic compounds (VOCs) composition to distinguish these samples. Such situations are often found for hybrid fruit. Sweetie is a hybrid of grapefruit and pummelo. Sweetie fruit is characterized by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In such cases where a volatile compound was identified as one of a couple possibilities (e.g., rlimonene or s-limonene), the concentration value was assigned to both odorants. Our literature review included headspace volatile analyses from several vegetables (carrot, tomato, and cucumber [38][39][40][41]), fruits / fruit juices (blueberry, peach, tangerine, tangerine peel, grapefruit, strawberry, strawberry sepals, orange juice, apple, quince, litchi, and loquat [40,[42][43][44][45][46][47][48][49][50]), spices (saffron, black and white pepper, cinnamon, and nutmeg [51]), and several other items (tea, almonds, cocoa beans, animal urine, bread, olive oil, truffles, and pine needles [40,[52][53][54][55][56][57][58][59]).…”
Section: Human Thresholds and Source Concentrationsmentioning
confidence: 99%
“…In such cases where a volatile compound was identified as one of a couple possibilities (e.g., rlimonene or s-limonene), the concentration value was assigned to both odorants. Our literature review included headspace volatile analyses from several vegetables (carrot, tomato, and cucumber [38][39][40][41]), fruits / fruit juices (blueberry, peach, tangerine, tangerine peel, grapefruit, strawberry, strawberry sepals, orange juice, apple, quince, litchi, and loquat [40,[42][43][44][45][46][47][48][49][50]), spices (saffron, black and white pepper, cinnamon, and nutmeg [51]), and several other items (tea, almonds, cocoa beans, animal urine, bread, olive oil, truffles, and pine needles [40,[52][53][54][55][56][57][58][59]).…”
Section: Human Thresholds and Source Concentrationsmentioning
confidence: 99%
“…The decrease in concentrations of fatty acids (see next paragraph) in the overripe period might be the reason for this delay. Fragment of monoterpenes [13,25] 1 VOCs tentative identifications were concluded based on the corresponding relationships and fragmentation patterns of previous research.…”
Section: Dynamic Changes Of Vocsmentioning
confidence: 94%
“…The concentrations of these m/z showed a significant increase in the overripe period (Figure 4 H-J). Monoterpenes and their fragments have been observed in the research on citrus and mangoes [25,42]. Accurate identification of some compounds, especially isomers, is a problem for PTR-MS. Getting the inspiration from selected ion flow tube mass spectrometry (SIFT-MS), researchers have modified PTR-MS with switchable reagent ion (SRI) to overcome this problem [43].…”
Section: Dynamic Changes Of Vocsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTR-TOF-MS was also utilized to obtain the mass-resolved fingerprints of VOCs of three species of citrus fruit (grapefruit, pummelo, and sweetie). 192 The application of the PCA allowed to select volatile organic compounds characteristic for a studied citrus species. Based on the obtained results, they concluded that esters and acetic acid were associated with pummelo samples, while limonene and linalool were related to grapefruit and sweetie samples, respectively.…”
Section: Instrumental Analytical Methodsmentioning
confidence: 99%